HASIL-HASIL RUMUSAN INTERNASIONAL WOLRD MUSLIM CONFERENCE ON EDUCATION TENTANG PENDIDIKAN DALAM ISLAM - Rasyid Rasyid; Farida Y. Mardliyah; Masruroh Lubis (STAI Asy-Syukriyyah, 2021)
The background of the birth of the International World Muslim Conference On Education is that Saudi Arabia wants to achieve the development of education and other fields like western countries that have already made developments. In addition, there are concerns over secular understandings from western countries for Saudi Arabia and in other Islamic countries. The method in this research is descriptive-interpretative qualitative method. This type of research is library research. From the results of the literature review that the author did, there were also 8 (eight) times the implementation of the International World Muslim Conference On Education from 1977 to 2012. The results of the formulation obtained from the International World Muslim Conference On Education are the definition of education, curriculum, teaching methods, textbooks. , plans and guidelines for learning, science and technology and evaluation